Synthesis of time-bin entangled states via tailored group velocity matching - U'ren, AB; Erdmann, R; Walmsley, I (2005)
We show that tailored group velocity matching in non- linear chi((2)) crystal sequences interspersed with birefringent chi((1)) compensators can be used to generate time-bin entangled states. By choosing the crystal and compensator materials appropriately it is possible to generate all four time-bin Bell states without resorting to time non- stationary devices. This scheme, in addition, lends itself well to the generation of higher-dimensionality states such as time-bin qutrits.